Can a skeptic be pious and why would he be? Lessons from ancient Pyrrhonism - Stojanović Pavle (Belgrade Philosophical Annual)
The Pyrrhonian skeptics argue that we should suspend belief about everything because, according to them, there are mutually exclusive accounts for and against every object of investigation, and because there are no good reasons to prefer either of the two positions. They also think that this suspension results in ataraxia, a mental state in which the skeptic is free from all unnecessary disturbance. Since ataraxia is also meant to apply to the matters pertaining to religion, it would seem to follow that the skeptic would be disinterested in taking any kind of position towards piety. But, this is not what we are told by our chief Pyrrhonian source, Sextus Empiricus. On the contrary, he says that the skeptic, as a follower of "ordinary life", and laws and customs of the society he lives in, will act piously, will say that gods exist, and will engage in the relevant religious practices. In this essay I argue that there is a way in which a skeptic can be pious without abandoning his skeptical approach, and that the main motivation for his piety is avoiding beliefs that challenge the customs of his theistic society because such beliefs would jeopardize the goal of achieving ataraxia.